Prevalence of infections with potential for vertical transmission in pregnant women seen ata University Hospital in southern Brazil - Gonçalves, Carla V.; Peres, Anna Carolina A; Zatt, Daniel B; Zanella, Natália do C; Schneider, Eliana I; Daros, Patrícia (Medicina (Ribeirao Preto), 2016)
Study design: This is a retrospective study using chart review at the Medical File and Statistics Service (SAME) of the University Hospital Dr. Miguel Riet Corrêa Jr. (HU-FURG) of women admitted in the service and Gynecology Obstetrics 01/01/2011 to 31/12/2012. Objective: To evaluate the prevalence of infections potentially transmitted vertically in pregnant women seen at a University Hospital. Methods: Only medical records of pregnant women hospitalized for childbirth or abortion were considered for analysis; charts from women not living in the city were excluded. A structured precoded questionnaire was completed with data obtained from the Live Birth Declaration and/or the admission record of the patient. The diagnosis of infection confirmed by tests performed on admission in the attached chart. A crude and adjusted analysis was performed with the calculation of the 95% confidence intervals, p-value for the chi- square test in SPSS 19.0 program. Results: Seventy-seven (77) of the 1070 women included in the study had an infection being 31 (2.9%) HIV, 29(2.7%) syphilis, 11 (2%) IgM toxoplasmosis, 5(0.55) Hepatitis C, 2 (0.2%) Hepatitis B and 2 co-infection. The adjusted risk analysis showed that women with less than five pre-natal visits or none had 2 and 5 times higher risk of infection respectively. Conclusions: A high prevalence of infections with the potential for vertical transmission, especially HIV and syphilis was observed. It is worth remarking that women that do not seek for prenatal care are more likely to have an infectious disease